Severe Antiphospholipid Syndrome and Diffuse Glomerulonephritis After Adalimumab Treatment in a Patient With Ulcerative Colitis - Ileana Rivera-Burgos; Luis M. Vilá (Case Reports in Rheumatology)
Tumor necrosis factor alpha inhibitors (TNFi) are biological drugs used worldwide to treat various autoimmune disorders. Paradoxically, TNF-α antagonists can also induce autoimmune diseases being systemic vasculitis, systemic lupus erythematosus, and psoriasis, the most common. We present a 22-year-old woman with ulcerative colitis (UC) who was started on adalimumab 40 mg subcutaneously every 2 weeks. After two doses of adalimumab, she developed gangrene of all toes and acute kidney injury requiring hemodialysis. Skin biopsy showed thrombi in the small vessels of the dermis. Renal biopsy disclosed diffuse proliferative glomerulonephritis (GN) and acute tubulointerstitial nephritis. Serologic work-up showed positive IgG anticardiolipin (ACL) antibodies and low C3 levels. Antinuclear, anti-dsDNA, anti-Smith, anti-SSA, anti-SSB, anti-RNP, antineutrophil cytoplasmic antibodies, ACL (IgA and IgM), and anti-β2-glycoprotein I (IgG, IgM, and IgA) antibodies were not elevated. Lupus anticoagulant test and cryoglobulins were negative. Adalimumab was discontinued, and she was treated with enoxaparin, intravenous (IV) methylprednisolone pulse, IV cyclophosphamide, and plasmapheresis followed by maintenance therapy with warfarin, prednisone, azathioprine, and hydroxychloroquine. She did not have further thrombotic events, and the acute kidney injury completely resolved. ACL IgG antibodies decreased to normal levels, and repeated tests were negative. After 7 years, anticoagulation and immunosuppressive drugs were discontinued. During a follow-up of 24 months, she remained in complete clinical remission. This report highlights the occurrence of autoimmune disorders induced by TNFi. Thus, careful monitoring of adverse immune reactions to TNFi is highly recommended.